Kira-kira - Kadohata, Cynthia (New York : Atheneum Books for Young Readers, 2004)
Chronicles the close friendship between two Japanese- American sisters growing up in rural Georgia during the late 1950s and early 1960s, and the despair when one sister becomes terminally ill.
740
Accelerated Reader AR
Newbery Medal, 2005
Keywords: Sisters -- Juvenile fiction; Newbery Medal; Friendship -- Juvenile fiction; Japanese Americans -- Juvenile fiction; Death -- Juvenile fiction; Georgia -- History -- 20th century -- Juvenile fiction